Characterization of a mcr-1 and CRISPR-Cas System Co-harboring Plasmid in a Carbapenemase-Producing High-Risk ST11 Klebsiella pneumoniae Strain - Cheng, Yi-Hsiang; Chou, Sheng-Hua; Huang, Po-Han; Yang, Tsuey-Ching; Juan, Yu-Fan; Kreiswirth, Barry N.; Lin, Yi-Tsung; Chen, Liang (Frontiers in Microbiology, 2021)
We set out to study the prevalence of the mcr-1 gene in carbapenemase-producing Klebsiella pneumoniae (CPKP) strains, and to determine whether its presence is associated with a fitness cost. A total of 234 clinical CPKP isolates were collected from a tertiary medical center in Taiwan from 2018 January to 2019 January. The mcr-1 and carbapenemase genes were detected by PCR followed by Sanger sequencing. The mcr-1-positive carbapenemase-producing strain was characterized by whole genome sequencing, a plasmid stability test and a conjugation assay. In vitro growth rate and an in vivo virulence test were compared between the parental mcr-1-positive strain and its mcr-1 plasmid-cured strain. We identified only one mcr-1 positive strain (KP2509), co-harboring blaKPC-2 and blaOXA-48, among 234 (1/234, 0.43%) CPKP strains. KP2509 and its Escherichia coli mcr-1 transconjugant showed moderate colistin resistance (MIC = 8 mg/L). The mcr-1 is located on a large conjugative plasmid (317 kb), pKP2509-MCR, with three replicons, IncHI, IncFIB and IncN. Interestingly, a complete Type IV-A3 CRISPR-Cas system was identified in pKP2509-MCR. Plasmid pKP2509-MCR was highly stable in KP2509 after 270 generation of passage, and the pKP2509-MCR cured strain PC-KP2509 showed similar growth rate and in vivo virulence in comparison to KP2509. The prevalence of mcr-1 in CPKP strains remains low in our center. Notably, we identified a large plasmid with multiple replicons containing both the mcr-1 and the Type IV-3A CRISPR-Cas genes. The further spread of this highly stable plasmid raises concern that it may promote the increase of mcr-1 prevalence in CPKP.